Biosystematic and chemosystematic studies in five South American species of Conyza (Asteraceae) Estudios biosistemáticos en cinco especies sudamericanas de Conyza (Asteraceae) - Juan D. Urdampilleta; Aníbal G. Amat; Claudio J. Bidau; Nicolás Kolb Koslobsky (Boletín de la Sociedad Argentina de Botánica, 2005)
The composition of the essentials oils of five species of Conyza Less from Argentina was determined by Gas Chromatography-Mass Spectrometer. This composition is associated to morphological and cytogenetic characters. The monoterpenes constitute more than 60% of the essential oils in C. blakei, C glandulitecta, C. sumatrensis var. sumatrensis and C. sumatrensis var. floribunda, in which limonene is the predominant compound. In C. bonariensis and C. primulaefolia the monoterpene content constitute less than the 40%. C. bonariensis presents only 13% limonene, while in C. primulaefolia it is absent. The similarity analysis of monoterpenes showed a relationship between the morphological and cytogenetic analysis, and the monoterpene content character seems to be important in biosystematic studies of the group studied. In general, C. sumatrensis var. sumatrensis is the species with more ancestral characters, while C. bonariensis and C. primulaefolia show more derived ones. Fueron determinados mediante Cromatografía Gaseosa - Espectrómetro de Masa los componentes de los aceites esenciales de seis especies de Conyza Less. de Argentina. Esta composición es asociada a caracteres morfológicos y citogenéticos. Los monoterpenos constituyen mas de 60% de aceites esenciales en C. blakei, C glandulitecta, C. sumatrensis var. sumatrensis, C. sumatrensis var. floribunda, en las cuales limoneno es el componente predominante. En C. bonariensis y C. primulaefolia el contenido de monoterpenos constituye menos de 40%. C. bonariensis presenta solo 13% limoneno, mientras que en C. primulaefolia este compuesto esta ausente. El análisis de similitud utilizando monoterpenos muestra relación con el análisis dado por caracteres morfológicos y citogenéticos, por lo que el carácter contenido de monoterpeno resulta importante en estudios biosistemáticos en el grupo estudiado. En general, C. sumatrensis var. sumatrensis es la especie que presenta un mayor numero de caracteres ancestrales, mientras que C. bonariensis y C. primulaefolia revelarían caracteres derivados.